Perbedaan Skala Nyeri Kala I Dan Durasi Kala II Persalinan pada Primigravida dengan Senam dan Yoga Kehamilan - Annisa Rifdatul Marwa; Sumarah Sumarah; Tri Maryani (Poltekkes Kemenkes Yogyakarta, 2017)
Labor pain is pain that comes from uterine contractions to try to remove the baby. The mother's perception of pain during childbirthcan affect the length of labor. First stage of labor has a longer duration for primigravidae, it causes pain experienced maternal lastslonger. Pain causes tachycardia in mothers (especially during the pushing in the second stage of labor), increased oxygenconsumption, production of lactic acid (lactate), the risk of hyperventilation with respiratory alkalosis, and increased muscle tensionskeletar. Pregnant women should be supported to carry out physical exercise to benefit during pregnancy and childbirth. There aresome physical exercise during pregnancy, which is often followed by pregnant women as pregnancy exercise and pregnancy yoga.The second difference lies in the physical exercise breathing. The purpose of this study to know the difference pain scale andduration of the first stage second stage of labor in primigravida which follows pregnancy exercise and pregnancy yoga. This studyused a prospective cohort design with purposive sampling technique. Subjects were primigravida trimester III who followed in RSIARachmi pregnancy exercise and pregnancy yoga at the Hospital AMC inApril-May 2017 amounted to 20 people for each group. Dataanalysis using Independent t test and Mann-Whitney test. The analysis showed no difference in the pain scale between primigravidthe first stage pregnancy exercise and yoga pregnancy (p-value 0.001) and there was no difference in the duration of the secondstage between primigravida pregnancy exercise and yoga pregnancy (p value 0.079).